Islamische Stammesgesellschaften Tribale Identitäten im Vorderen Orient in sozialanthropologischer Perspektive - Kraus, Wolfgang (2004)
This book is the first comprehensive study in German on tribal identity in the Middle East. It includes a comparative and theoretical survey of Muslim tribal societies and a detailed empirical case-study. A separate identity within wider political and cultural communities is one of the most characteristic aspects of Middle Eastern tribes. It is typically expressed in tribal striving for political autonomy - an autonomy practically realized in varying degrees according to historical conditions. The book examines cultural dimensions and practical manifestations of tribal identity in this tension between local particularism and wider belonging. A critical discussion of the anthropological notion of tribe serves as an introduction to the theoretical part of the book. The insight that the most important common traits of Muslim tribes are located in the cultural and ideological sphere leads on to an examination of the general characteristics of Middle Eastern tribal societies. Then specific cultural models of tribal identity, such as the ideological and practical role of kinship and marriage relations, are examined, and the highly variable practical manifestations of tribal organization are outlined. The first part of the book is concluded by a critical appraisal of competing theoretical approaches to the phenomenon of tribal identity, which forms the basis for the empirical case study. In the second part, the theoretical approach elaborated in the first part is applied to a case study of a specific tribal society, a central Moroccan Berber tribe. First, the historical and geographical conditions are analyzed. Then the history of the tribe and the various kinds of sources for its understanding are discussed. Further chapters are devoted to the traditional political and legal institutions and their transformations in the course of the 20th century. The hierarchically ordered local status categories and the segmentary structure of the tribe are analyzed in detail. Finally, an investigation of orally transmitted historical knowledge shows that the local discourse about the past is a privileged domain for the study of the ideologies and cultural conceptions that constitute local tribal identity but also contribute to limiting and transcending it. An important methodological principle followed throughout is that ruptures and contradictions should not be ignored or explained away. The oral historical discourse not only provides an insight into the meaning of tribal identity. It also shows how covertly the dominant ideological models are called into question time and again. Even on the cultural and ideological level, tribal identity can only be understood in its interrelations with the wider identity relating to the Muslim state - interrelations that must be explained as historically conditioned and variable.